Analisa Kebutuhan Mahasiswa Manajemen Terhadap Materi Pembelajaran Bahasa Inggris - Evi Kasyulita; Andri Donal; Rivi Antoni; Batdal Niati; Eripuddin Eripuddin (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
To achieve effectiveness and alignment between the needs and the ability of students, it is necessary to conduct research about the needs of management students in learning English, especially English for Specific Purposes. Before designing the material for language teaching, the teacher needs to understand the nature of the material development and the process that is typically involved if quality materials are to be created. This research was designed as a descriptive qualitative design. In collecting the data, researchers gave questionnaires and interview the first semester of Management students at the University of Pasir Pengaraian. There are 80 students as a sample to conduct this research. The finding of this research there is six topics that students need to study in English there was an introduction about ourselves, introducing people, how to be a presentation, how to make the application letter, how to explain something, how to make something